The death of character - Fuchs, Elinor (Bloomington Indiana University Press, 1996)
"Extremely well written, and exceedingly well informed, this is a work that opens a variety of important questions in sophisticated and theoretically nuanced ways. It is hard to imagine a better tour guide than Fuchs for a trip through the last thirty years of, as she puts it, what we used to call the 'avant-garde.'" -- Essays in Theatre